Pairing behaviour in a colony of Mute Swans Cygnus olor - Perrins, C M; McCleery, R H (Wildfowl, 1996)
A study was made of the Mute Swans present in the breeding colony at Abbotsbury each summer. A large number of the birds do not breed. Some of these non-breeders are probably not yet old enough to breed, but others are birds which have bred in earlier years. In years of low nesting numbers, the numbers of birds which have bred, but are not breeding, may exceed the numbers of breeders. When swans take a new mate, due to death or divorce from the previous mate, they tend to choose a mate closer to their own age than would be expected by chance.